Perimetric demonstration of spontaneous visual field recovery following occipital lobe haemorrhage. (29th August 2013) - Lin, Siying; George, Badie Z; Wilson-Holt, Nicholas J
Abstract : A 45-year-old patient on lifelong warfarin therapy after a metal aortic valve replacement developed a homonymous visual field defect following an occipital lobe haemorrhage. The patient received only conservative management and yet described continued improvement in her visual field defect for up to 20 months following the initial cerebral insult. We present the first conclusive illustrative documentation of visual recovery in a patient with an occipital lobe haemorrhage with sequential automated perimetric assessments over an extended period of time.